THE ACTIVE LEARNING APPROACH TO SMP BAYT AL-HIKMAH STUDENTS : A CASE STUDY OF LEARNING ISLAMIC RELIGIOUS EDUCATION IN ISLAMIC BOARDING SCHOOLS - Puspitaningrum, Puspitaningrum; Mansur, Rosichin; Hakim, Dian Mohammad (JURNAL TARBIYAH, 2023)
A learning approach that is fun, flexible, friendly to students, and in accordance with the needs of students is a learning approach that humanizes humans. Researchers used qualitative research methods with a case study approach. Data search techniques use participant observation, in-depth interviews, and document studies. The purpose of this article is to describe the planning of Islamic religious education learning, the implementation of Islamic religious education learning, and the learning outcomes of Islamic religious education. The results of the study illustrate that: (1) Islamic religious education learning planning using an active learning approach is realized through: (a) the selection of subject matter is carried out through joint meetings to integrate the Islamic boarding school curriculum and the formal curriculum; (b) the facilitator teaches using project learning methods, experiments, and field trips; (c) the learning model for students is project-based, learning information research, mind mapping, jigsaw puzzles, and index card matches; and (d) evaluation of student learning in the form of written tests, oral tests, and cognitive evaluations. (2) Implementation of Islamic religious education learning using an active learning approach has five aspects namely: (a) active participation of students in learning; (b) interrelation of students' experiences for intellectuality and action; (c) centered on students that all students learn as learning subjects; (d) new perspectives of students during the learning process students are able to think critically, discuss, and develop Islamic character; and (e) conducive and dynamic social interaction can be seen from the facilitator teaching learning approaches through discussions, lectures, demonstrations, experiments, and blended learning, project-based learning, information research learning, mind mapping, jigsaw puzzles, and index card matches. (3) The results of learning using an active learning approach are reflected in three aspects, namely: (a) changes in the behavior of students who are more comfortable in class; (b) increased knowledge of students in critical thinking, discussing, and collaborating in learning; and (c) a new habit pattern is formed for the students to have an Islamic personality, have manners, the students are more active, and the students are capable in debating and arguing.